การพัฒนาไบโอเซนเซอร์เพื่อตรวจสอบการแสดงออกของยีน : กรณีศึกษาของยีนกลูโคซิลทรานสเฟอเรส (RhGT1) ในกุหลาบ - อภิลดา โอเจริญ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Method for glucosyl transferase gene (RhGT1) expression detection was developed based on signal measurement from free electron of Hoechst 33258 on carbon screen printed electrode, area 2.63 mm². Results revealed anodic current peak changes in between 0.85-2.1 µA. The minimum anodic current indicated maximum RhGT1 gene expression. When RhGT1 gene expression was determined at all 5 flowering stages 0, 2, 4, 6 and 8 days of development, it was found that maximum RhGT1 gene expression in term of cDNA copy numbers was detected at 4 day of development stage at 79.06% compared with that of 18S housekeeping gene. In flower stage of 6, 8, 2 and 0 day gene expression was 69.81, 64.50, 16.12 and 6.66 respectively. The finding that maximum RhGT1 gene expression found at 4 day stage was in corresponding with stage of one day prior to the physiological color changes. This studies indicate the potential application of biosensor in semiquantitative gene expression study and constitute basis for its technical applicate to other economic flowers